2003
DOI: 10.1034/j.1399-0004.2003.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between SREBP‐1a and APOB polymorphisms influences total and low‐density lipoprotein cholesterol levels in patients with coronary artery disease

Abstract: In this study, we examined the insertion/deletion (Ins/Del) and XbaI polymorphisms of the apolipoprotein B (APOB) gene and the -36delG polymorphism in the sterol regulatory element binding protein-1a (SREBP-1a) gene in 298 patients with non-diabetic angiographically assessed coronary artery disease (CAD), and 188 healthy controls, from a Brazilian population of European descent. Del/X+ haplotype carriers had higher levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) in patients (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
2
13
0
2
Order By: Relevance
“…The homozygotes for the alleles T and Del had higher levels of these lipids than individuals heterozygous for both alleles, who had intermediate levels; this result is compatible with a co-dominant effect of these polymorphisms. These results are in agreement with published data showing that the Del and T alleles are associated with increased levels of TC and/or LDL-C in different populations with distinct diseases [9, 3537]. However, Xu et al and Ye et al found no association of the polymorphism in the signal peptide of the gene with TC and LDL-C levels in the Finnish and Chinese populations, respectively [38, 39].…”
Section: Discussionsupporting
confidence: 92%
“…The homozygotes for the alleles T and Del had higher levels of these lipids than individuals heterozygous for both alleles, who had intermediate levels; this result is compatible with a co-dominant effect of these polymorphisms. These results are in agreement with published data showing that the Del and T alleles are associated with increased levels of TC and/or LDL-C in different populations with distinct diseases [9, 3537]. However, Xu et al and Ye et al found no association of the polymorphism in the signal peptide of the gene with TC and LDL-C levels in the Finnish and Chinese populations, respectively [38, 39].…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to that found in other populations (SREBF1: 51%-63%; SCAP: 43%-53%) [16,18,19,32,33].…”
Section: Patient Datasupporting
confidence: 91%
“…23 Considering this finding and the strong LD in the region around SREBF1 on 17p11.2, it is possible that the association observed with the RAI1 marker is actually picking up signal from a SREBF1 variant, or vice versa. In dbSNP (http:// www.ncbi.nlm.nih.gov/projects/SNP/) and the scientific literature, several SNPs have been reported to change the amino acid composition of SREBP1 or to influence the level of cholesterol synthesis, [24][25][26] but none of these SNPs are deposited in HapMap and we have therefore not been able to conclude on their LD to the associated SNPs of the present study. The SREBF2 gene is located on chromosome 22q13.2.…”
Section: Discussionmentioning
confidence: 84%